Assessment of Environmental and Social Impact of Benin-delta Power Transmission line Expansion Project - M. A. S. Horsfall; A. A. Obafemi; A. I. Hart (Archives of Current Research International, 2023)
This study examined the environmental and social impacts and household vulnerability of the 107 km Benin-Delta (Ughelli) 330 kV power transmission line (TL) expansion project right of way (ROW). Questionnaires were administered to 56 communities and 344 households to obtain information on their livelihood and the perceived environmental and social impacts of the TL expansion. Results revealed the TL on land use, community socio-cultural and health Status, employment and opportunities, community agitation and social economic status, they were found to be high, low, beneficial, medium and low in that order. Loss of land and economic trees were identified as the highest impacts of the project. All communities within the sphere of influence of the project had encroached on the existing ROW. The most vulnerable groups affected by the project are the non-indigenous elderly, widows and female-headed households, children, herdsmen, unemployed and those that have lost their lands and are now without means of livelihood. The valuation of assets and losses suffered suggests the need for resettlement and compensation. Specific mitigation measures which could help ameliorate suffering of the economically vulnerable households should be put in place.